KONSUMSI SEBAGAI PENANDA KESEJAHTERAAN DAN STRATIFIKASI SOSIAL (Dalam Bingkai Pemikiran Jean Baudrillard) - Ulfa, Nurist Surayya (Faculty of Social and Political Sciences Diponegoro University)
Abstract: Consumption has become one of the most significant matters in the modern life, that people can not live without consuming. This is the result of social construction to perceive consumption as a way of pursuing happiness, which means that everyone as the member of modern society is obliged to take a part of it. However, what people consumed is not as simple as fulfilling the needs, but more about the signs attached to what they are consumed. This writing is about the social logic of consumtion as explained by Jean Baudrillard. He described consumption as a process of social signification, communication, Â classification and differentiation. People use consumption as a language. They consume signs to identify the social welfare and social stratification.Keyword: Consumerism, consuming sign, identification, social stratification.permalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3203